2010
DOI: 10.1029/2010gl043543
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for generation of ULF waves by ionospheric heating

Abstract: [1] We present results from a numerical study of the generation of ULF waves by the ionospheric feedback instability (IFI) initiated by heating the ionosphere with a powerful HF transmitter. Previous investigations in this area suggested that even a relatively weak modification of the ionospheric conductivity by the heater can initiate IFI and enhance its development, if the heating wave is modulated with a frequency of the most feedback-unstable ULF mode. In this paper, we show that the development of the ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 18 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…These assumptions work well for modeling heating experiments when the background conductivity is relatively high (≥ 5-10 mho), and the amplitude of the waves/FACs is relatively small (j ≤ 1 µA m −2 ). When the background density is low and/or the amplitude of the waves reaches significant amplitudes the Hall conductivity should be taken into the consideration and the ionospheric boundary condition should incorporate effects of active magnetosphere-ionosphere interactions (the so-called ionospheric feedback mechanism), e.g., Streltsov and Pedersen (2010).…”
Section: Modelmentioning
confidence: 99%
“…These assumptions work well for modeling heating experiments when the background conductivity is relatively high (≥ 5-10 mho), and the amplitude of the waves/FACs is relatively small (j ≤ 1 µA m −2 ). When the background density is low and/or the amplitude of the waves reaches significant amplitudes the Hall conductivity should be taken into the consideration and the ionospheric boundary condition should incorporate effects of active magnetosphere-ionosphere interactions (the so-called ionospheric feedback mechanism), e.g., Streltsov and Pedersen (2010).…”
Section: Modelmentioning
confidence: 99%
“…Variations in α ( y , t ) would then serve as a proxy for the effects of an ionospheric heater. A study of this type has already been performed by Streltsov and Pedersen [2010] in a search for effective methods to generate magnetospheric Alfvén waves by ionospheric heating. Those authors observed that E‐region density features (produced by heating) move in the direction of the electric field at a characteristic speed, and a stronger system response is produced when the region of ionospheric heating itself moves at this speed.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical simulations of the electron MHD equations in the dipole magnetic field geometry revealed that the amplification takes place more efficiently when the frequency of the whistler mode waves (in the frequency range from 0.5 to 1.0 kHz) changes in the equatorial magnetosphere at the rate of 0.25 to 0.47 kHz/s. The maximum amplification occurs when this rate is 0.33 kHz/s, and no/very little amplification was observed when this gradient is equal to 0 or when it is larger than 0.78 kHz/s [Streltsov et al, 2010].…”
Section: Elf/vlf Waves In the Magnetospherementioning
confidence: 95%
“…magnetic field in the direction of the background electric field and reaching maximum amplitude not at the location where the instability started (or where the heating initiates the instability), but further down in the direction of the background electric field. Streltsov and Pedersen [2010] showed with numerical simulations that IFI develops significantly faster when the heating occurs with a constant beam (not modulated in time with any frequency) and the spot is moving in the direction of the background electric field with the phase velocity of the wave. This velocity can be approximately estimated from the ion mobility and the magnitude of the electric field in the ionosphere.…”
Section: Ulf Waves In the Global Magnetospheric Resonatormentioning
confidence: 95%
See 1 more Smart Citation